We are supposed to solve the equation
![6(2x-1)-12=3(7x+4)](https://img.qammunity.org/2023/formulas/mathematics/college/o9sz76fbkhsokt99qn701ztmmjr33yjzvq.png)
Here, we need to apply the distributive laws on both sides.
Comment: The distributive laws say that
![a(b+c)=ab+ac\text{ and }(b+c)a=ba+ca](https://img.qammunity.org/2023/formulas/mathematics/college/s1jp3w67lhxweo4yapyt72q70xqn88wyiz.png)
Using this comment we get
![6(2x-1)=6(2x)+6(-1)=12x-6](https://img.qammunity.org/2023/formulas/mathematics/college/slhei5ge24e9el8087bac71bkudkjwv32f.png)
![3(7x+4)=3(7x)+3(4)=21x+12](https://img.qammunity.org/2023/formulas/mathematics/college/pd35szd8yn0v7k2u16k9ey167xpmxx7lmf.png)
Then, our equation becomes
![(12x-6)-12=21x+12](https://img.qammunity.org/2023/formulas/mathematics/college/2bnmt91be4jrocpn7lig1h1pi6tk0aveai.png)
![12x-18=21x+12](https://img.qammunity.org/2023/formulas/mathematics/college/lmtgx0uip0bzsvlzzav2l1alre6ez9dys7.png)
Now, let's apply the rule: terms with x on the right-hand side, and the rest on the left-hand side, to obtain
![-18-12=21x-12x](https://img.qammunity.org/2023/formulas/mathematics/college/7gd6si6w4rf43ozvg92kn129qmbzkeyd83.png)
![-30=9x](https://img.qammunity.org/2023/formulas/mathematics/college/b0mehz3lnpegbg1spq0h19sf1vv6g7mc3j.png)
![x=(-30)/(9)=-(10)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/wic3b1000mb90nck455z534azz6hnm0li0.png)